How to Eat the Elephant in the Legal Academy - Rozelle, Susan D. (Columbia Journal of Gender and Law, 2015)
Persistent discrimination is one of the elephants in the legal academy. We need to eliminate it, and we all know that the only way to eat an elephant is one bite at a time. So here goes: I’m Susan Rozelle, and I have begun to note all the ways in which United States law schools’ institutional culture presumes the Ideal Worker: white, male, middle-class, middle-aged, and married to a woman who manages his home and his family life for him. We blindly continue to follow a variety of existing structural systems that both create and reinforce challenges for the many members of our community who fail to meet this embedded stereotype.